Local Features of Ballads in Northeast Siberia: Plots of ‘The Mother-in-Law Held Captive by Her Son-in-Law’ and ‘Prince Volkonsky and the Gatekeeper’ - O. I. Charina (Научный диалог, 2023)
This article aims to clarify the characteristics of the ballad genre among other works in Northeast Siberia (in Yakutia and a separate settlement in the Magadan region). It examines the local features of ballad song variants recorded from long-time residents of Northeast Yakutia. The source materials used are texts published in the collections “Folklore of Russian Ustye” (1986) and “Russian Epic Poetry of Siberia and the Far East” (1991). The article presents ballad songs of Russian settlers from the lower reaches of the Indigirka River and the Kolyma River basin. Recordings by D. I. Melikov and V. G. Bogoraz are also utilized. The study is conducted using descriptive and comparative methods, as well as some techniques of lexical-semantic analysis. The work continues the research related to specifying the repertoire, genre, and stylistic features that constitute the uniqueness of epic poetry in Northeast Yakutia recorded in the 19th-20th centuries. The specifics of their dissemination are characterized. The first recordings made in the 19th century are compared with ballad texts documented in the 20th century. Special attention is given to the ballad song “The Mother-in-Law Held Captive by Her Son-in-Law.” It is noted that this folklore specimen reflects certain historical realities related to the area where the song was circulated. It is reported that ballad texts were lost by the 1970s.